Supine vs. Prone Position With Turn of the Head Does Not Affect Cerebral Perfusion and Oxygenation in Stable Preterm Infants ≤32 Weeks Gestational Age - Spengler, Dietmar; Loewe, Elisa; Krause, Martin F. (Frontiers in Physiology, 2018)
Intraventricular hemorrhage (IVH) is a frequent major damage to the brain of premature babies ≤32 weeks gestational age, and its incidence (20–25%) has not significantly changed lately. Because of the intrinsic fragility of germinal matrix blood vessels, IVH occurs following disruption of subependymal mono-layer arteries and is generally attributed to ischemia-reperfusion alterations or venous congestion, which may be caused by turn of the head. Therefore, supine position with the head in a midline position is considered a standard position for preterm infants during their first days of life. We asked whether a change in body position (supine vs. prone) linked with a turn of the head by 90° in the prone position would change blood flow velocities and resistance indices in major cerebral arteries and veins of stable premature babies at two different time points (t0, day of life 2, vs. t1, day 9). Moreover, we assessed cerebral tissue oxygenation (cStO2) by near-infrared spectroscopy and determined correlations for changes in velocities and oxygenation. Twenty one premature infants [gestational age 30 (26–32) weeks] with sufficiently stable gas exchange and circulation were screened by ultrasonography and near-infrared spectroscopy. Peak systolic and end-diastolic blood flow velocities in the anterior cerebral arteries (29 ± 6 m/s vs. 28 ± 7 peak flow at t0, 36 ± 8 vs. 35 ± 7 at t1), the basilar artery, the right and the left internal carotid artery, and the great cerebral vein Galen (4.0 ± 0.8 m/s vs. 4.1 ± 1.0 maximum flow at t0, 4.4 ± 0.8 vs. 4.4 ± 1.0 at t1) did not show significant differences following change of body and head position. Also, there were no differences in cStO2 (83 ± 7% vs. 84 ± 7 at t0, 76 ± 10 vs. 77 ± 11 at t1) and in vital signs such as heart rate and blood pressure. We conclude that change in body position with turn of the head in the prone position does not elicit significant alterations in cerebral blood flow velocities or in oxygenation of cerebral tissues. Maturational changes in arterial flow velocities and cStO2 are not correlated. For this subgroup of premature infants at low risk of IVH our data do not support the concept of exclusive preterm infant care in supine position.